A Critical Reading of the Decisions of the Federal Supreme Court on the Continuity of the Work of the Provincial Councils and their Exercise of Legislative Jurisdiction - Rahman, Avin Khaled Abdel (Journal of Legal and Political Studies, 2022)
The Federal Supreme Court is the federal judicial organ in charge of protecting the constitution. This court has a notable role in protecting the powers that granted to the constituent units of the Iraqi federal state, including governorates not organized into a region. In this regards, the Iraqi constitution in the year 2005, granted several administrative and financial powers to these governorates to be able to manage and organize their affairs according to administrative decentralization which was confirmed with Article 122 , and these powers created a wide arguments in the political and legal level, particularly the powers issue for setting rules provincial councils , as well as the issue of the continuity of the work of these councils despite the ending of their legal term, which was the subject of an appeal in front of the Federal Supreme Court for more than once and by more than one side, even the court was amended some of its decisions and came up with changed rulings based on the idea of constitutional judicial reversal which defines (it is a clear and definite voluntary replacement for a new constitutional court ruling in place of a previous constitutional court for ruling in the same case subject which fits with the reality of society and its progress ).
Keywords: Federal Supreme Court; Iraqi federal state; Iraqi constitution; administrative decentralization; federal judicial organ